Implementasi Pendidikan Multikultural: Survei dalam Pembelajaran Bahasa Indonesia di SMA DKI Jakarta - Safi’i, Imam; Sobri, Sobri; Muljono, Hery; Fitri, Annisa Aprilia (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2024)
This study examines the implementation of multicultural education in Indonesian language learning in senior high schools in DKI Jakarta. This study uses a quantitative approach with a survey design. Respondents in this study were 377 senior high school students in the DKI Jakarta area. The aspects explored were related to students' perceptions of the implementation of multicultural education in Indonesian language learning, which include the formation of cultured people, teaching noble human values, respect for differences between students, and evaluation of learning related to cultural perceptions. The results showed that most students gave positive responses to the implementation of mutual education in Indonesian language learning. This study emphasizes the importance of ongoing support from stakeholders to ensure that multicultural education can be embedded in every aspect of school life. These findings suggest the need for further research to explore the impact of the implementation of multicultural education on students' attitudes and behaviors and the adaptation of learning models in facing the challenges of globalization. Thus, multicultural education is expected to form a young generation of Indonesia who are not only academically intelligent, but also wise in appreciating diversity.